2016
DOI: 10.1016/j.sab.2016.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of geological materials containing uranium using laser-induced breakdown spectroscopy

Abstract: Laser induced breakdown spectroscopy (LIBS) is a rapid atomic emission spectroscopy technique that can be configured for a variety of applications including space, forensics, and industry. LIBS can also be configured for stand-off distances or in-situ, under vacuum, high pressure, atmospheric or different gas environments, and with different resolving-power spectrometers. The detection of uranium in a complex geological matrix under different measurement schemes is explored in this paper. Although many investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…LA-OES (or LIBS) meets most of these criteria (rapid analysis, fieldable, no sample preparation), albeit with some challenges with regard to characterization and identification of nuclear materials (e.g., U). The electronic complexity of high-Z elements, or elements with high partition functions, such as U, generates congested spectra in which specific emission features are challenging to discern without high-resolution spectroscopic equipment [2,3,5,15,19,20]. Furthermore, samples may only contain trace amounts of U in a multiconstituent matrix, allowing emission features of more abundant target constituents to obfuscate those of U [13,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LA-OES (or LIBS) meets most of these criteria (rapid analysis, fieldable, no sample preparation), albeit with some challenges with regard to characterization and identification of nuclear materials (e.g., U). The electronic complexity of high-Z elements, or elements with high partition functions, such as U, generates congested spectra in which specific emission features are challenging to discern without high-resolution spectroscopic equipment [2,3,5,15,19,20]. Furthermore, samples may only contain trace amounts of U in a multiconstituent matrix, allowing emission features of more abundant target constituents to obfuscate those of U [13,18].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, LA-OES proves practical in detecting isotopic shifts of elements including U [21][22][23][24][25][26][27]. Reported U detection limits employing LA-OES are on the order of parts per million (ppm) [20,28,29]. However, previous investigations also suggest that the U signal varies significantly with ambient conditions using different LA spectrometric techniques [30].…”
Section: Introductionmentioning
confidence: 99%
“…Prior literature results report LODs for U over a wide range from 3–50,000 ppm 6, 2426, 28 in LIBS studies. The 2DFS showed enhanced emission intensity relative to LIBS by factors of 5–35×, resulting from LIF pumped by the ECDL.…”
Section: Resultsmentioning
confidence: 99%
“…Nuclear forensics is one such application where LIBS has found significant application [1]. Several studies have demonstrated the ability of LIBS to detect nuclear material in matrices relevant to the nuclear community, such as geological deposits [2,3], uranium ores [4,5], and surrogate nuclear debris [6]. Other studies validated the use of LIBS in nuclear safeguard applications, including analysis of IAEAswipe samples [7], nuclear reprocessing plant activities [8], and standoff detection of radiological threat materials [9].…”
Section: Introductionmentioning
confidence: 99%